Pedagogy & practice for online English language teacher education - Pawan, Faridah; Wiechart, Kelly A.; Warren, Amber N.; Park, Jaehan (Tesol Press, 2016)
"Pedagogy -- not technology -- drives effective online instruction. Online coursework for teacher education and professional development has significantly increased in popularity. It is cost efficient, can eliminate access barriers, and provides just-in-time, ongoing, and embedded support for busy teachers. However, researchers and educators often lament the lack of focus on pedagogical training for online instructors. This knowledge gap remains an area in need of more rigorous attention. The authors of this book discuss foundational theories of pedagogy and link those theories with their own practices in online courses for language teacher education and language teaching"--Page 4 of cover.